Stereoselective Transfer Semi‐Hydrogenation of Alkynes to E‐Olefins with N‐Heterocyclic Silylene–Manganese Catalysts - Zhou, Yu‐Peng; Mo, Zhenbo; Luecke, Marcel‐Philip; Driess, Matthias (Chemistry : a European journal, 2018)
The synthesis and structures of the first SiII‐donor supported manganese(II) complexes [L1]MnCl2, [L2]MnCl2, and [L3]2MnCl2 are reported, bearing a pincer‐type bis(NHSi)‐pyridine ligand L1, bidentate bis(NHSi)‐ferrocene ligand L2, and two monodentate NHSi ligands L3 (NHSi = N‐heterocyclic silylene), respectively. They act as unprecedented very active and stereoselective Mn‐based precatalysts (1 mol % loading) in transfer semi‐hydrogenations of alkynes to give the corresponding E‐olefins using ammonia–borane as a convenient hydrogen source under mild reaction conditions. Complex [L1]MnCl2 shows the best catalytic performance with quantitative conversion rates and excellent E‐stereoselectivities (up to 98 %) for different alkyne substrates. Different types of functional groups can be tolerated, except CN, NH2, NO2, and OH groups at the phenyl group of 1‐phenyl substituted alkynes. Give me the E: The first N‐heterocyclic silylene (NHSi)–manganese(II) complexes have been synthesized and fully characterized. Among them, the [L1]MnCl2 complex, which bear bis‐NHSi pyridine pincer ligand L1, acts as a superior precatalysts in homogeneous transfer semi‐hydrogenation of alkynes, using ammonia‐borane as a convenient hydrogen source at mild reaction conditions ([Mn]=[L1]MnCl2).